Pengaruh Pancasila Terhadap Pengaturan Hukum Adat dalam Konstitusi Indonesia Perspektif Historis dan Yuridis - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Ardwana Riswari Wisnu; Arif Budi Utomo; Inayatun Nafi'ah (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
As the basic ideology of the Indonesian state, Pancasila not only provides philosophical and normative guidelines for governance, but also plays an important role in the recognition and implementation of customary law throughout Indonesia. This study aims to provide an in-depth analysis of the relationship between Pancasila and customary law in the context of the Indonesian constitution, evaluating how Pancasila influences the recognition, regulation, and implementation of customary law, while exploring historical and legal challenges and solutions. This study also examines how regulations governing customary law should be adjusted to continue to respect customary norms while remaining consistent with national law and human rights. Through comprehensive analysis and strategic recommendations, this study aims to contribute to strengthening the integration of customary law into the Indonesian national legal system, strengthening the implementation of the principles of Pancasila, and promoting justice and harmony within the framework of a unitary state. This study aims to ensure that customary law is not only respected but also implemented effectively in supporting the basic values ​​of the state and the interests of indigenous peoples throughout Indonesia.